Human development - Craig, Grace J. (New jersey : Prentice hall, 1989)
Designed for students, this text takes a chronological and interdisciplinary approach to human development. With its focus on context and culture, the seventh edition illustrates that the status of human development is inextricably embedded in a study of complex and changing cultures.
Includes bibliographical reference and index.
Keywords: developmental psychology; Child Development; Human Development